Herbal tea induced hepatic veno-occlusive disease: quantification of toxic alkaloid exposure in adults. Issue 1 (January 1985) - Kumana, C R; Ng, M; Lin, H J; Ko, W; Wu, P C; Todd, D
Abstract : Four young Chinese women took daily doses of an unidentified 'Indian' herbal tea as treatment for psoriasis. Three (one of whom died), developed ascites, hepatomegaly and biochemical abnormalities within 19-45 days. The fourth patient discontinued herbal tea after 21 days when she developed a skin rash. Two patients had portal hypertension, while all had liver histology showing features of veno-occlusive disease. Pyrrolizidine alkaloids were identified spectrophotometrically in the brewed tea, and in the chopped leaves of the herbal mixture; the mean dose in the tea prepared for consumption being 12 mg/day of alkaloid base and 18 mg/day of N-oxide. The mean cumulative dose of alkaloids (base + N-oxide) before onset of symptoms (three patients), was estimated to be 18 mg/kg. In the asymptomatic patient with histological liver disease only, the corresponding dose was 15 mg/kg. These cases thus provide some measure of pyrrolizidine alkaloid toxicity in adults.